Comparison of Carotid Doppler Ultrasound to Other Angiographic Modalities in the Measurement of Carotid Artery Stenosis. Issue 6 (19th June 2018) - Boyko, Matthew; Kalashyan, Hayrapet; Becher, Harald; Romanchuk, Helen; Saqqur, Maher; Rempel, Jeremy L.; Derksen, Carol; Shuaib, Ashfaq; Khan, Khurshid
ABSTRACT: BACKGROUND AND PURPOSE: The purpose of this study was to compare Doppler ultrasound (DUS) to other angiographic modalities: computed tomography angiography (CTA), magnetic resonance angiography (MRA), and digital subtraction angiography (DSA). METHODS: All DUS studies performed at Stroke Prevention Clinic (SPC) from 2011 to 2013 and referred for further angiographic modalities were included. Patients were excluded if the corresponding angiographic modality was not performed within 6 months of DUS. Patients were also excluded if they underwent interventions before DUS or between the time of DUS and the corresponding angiographic modality. The degree of stenosis was classified as mild (<50%), moderate (50‐69%), severe (70‐99%), or occlusion (100%). RESULTS: In total, 245 patients were identified. Nine patients were excluded (3.7%). Overall 472 Doppler studies of single ICAs from 236 patients were included in our analysis. Age was 65 ± 13 years and 136 patients were males (57.6%). There was an excellent agreement between DUS and CTA (kappa = .9 [ P < .001], n = 274), good agreement with MRA (kappa = .8 [ P < .001], n = 242), and excellent agreement with DSA (kappa = .92 [ P < .001], n = 18). There was excellent agreement between CTA and MRA (kappa = .87, n = 46). CONCLUSION: Doppler ultrasound performed in a dedicated SPC by an experienced sonographer and reviewed by a certified stroke neurologist serves as a reliable initial screening tool in determining carotid artery stenosis.